Peptide-Enriched Silk Fibroin Sponge and Trabecular Titanium Composites to Enhance Bone Ingrowth of Prosthetic Implants in an Ovine Model of Bone Gaps - Lovati, Arianna B.; Lopa, Silvia; Bottagisio, Marta; Talò, Giuseppe; Canciani, Elena; Dellavia, Claudia; Alessandrino, Antonio; Biagiotti, Marco; Freddi, Giuliano; Segatti, Francesco; Moretti, Matteo (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoarthritis frequently requires arthroplasty. Cementless implants are widely used in clinics to replace damaged cartilage or missing bone tissue. In cementless arthroplasty, the risk of aseptic loosening strictly depends on implant stability and bone–implant interface, which are fundamental to guarantee the long-term success of the implant. Ameliorating the features of prosthetic materials, including their porosity and/or geometry, and identifying osteoconductive and/or osteoinductive coatings of implant surfaces are the main strategies to enhance the bone-implant contact surface area. Herein, the development of a novel composite consisting in the association of macro-porous trabecular titanium with silk fibroin sponges enriched with anionic fibroin-derived polypeptides is described. This composite is applied to improve early bone ingrowth into the implant mesh in a sheep model of bone defects. The composite enables to nucleate carbonated hydroxyapatite and accelerates the osteoblastic differentiation of resident cells, inducing an outward bone growth, a feature that can be particularly relevant when applying these implants in the case of poor osseointegration. Moreover, the osteoconductive properties of peptide-enriched silk fibroin sponges support an inward bone deposition from the native bone towards the implants. This technology can be exploited to improve the biological functionality of various prosthetic materials in terms of early bone fixation and prevention of aseptic loosening in prosthetic surgery.